PENERAPAN EDUTAINMENT DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL - Ika Nur’Aini (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
Learning must be designed in such a good way that it creates an atmosphere of learning in the classroom that feels comfortable, full of freedom without any pressure, and more fun learning. Therefore, one strategy that can make learning fun is Edutainment. Edutainment is a learning process designed by combining educational and entertainment content in harmony so that learning activities are fun. In other words, learning is done in a fun way, not otherwise boring and in a depressed state. The purpose of this paper is to know the application of edutainment in the learning of social sciences. The approach used in this paper is a case study in the form of descriptive. The result of this paper is that the application of edutainment in Social Science learning can be applied by varying with various learning methods such as role play or role playing, demonstration, and other learning games that are able to increase students' interest, motivation, and learning activities